2020
DOI: 10.3390/molecules25184111
|View full text |Cite
|
Sign up to set email alerts
|

Prevailing Knowledge on the Bioavailability and Biological Activities of Sulphur Compounds from Alliums: A Potential Drug Candidate

Abstract: Allium sativum (garlic) is widely known and is consumed as a natural prophylactic worldwide. It produces more than 200 identified chemical compounds, with more than 20 different kinds of sulfide compounds. The sulfide compounds particularly are proven to contribute to its various biological roles and pharmacological properties such as antimicrobial, antithrombotic, hypoglycemic, antitumour, and hypolipidemic. Therefore, it is often referred as disease-preventive food. Sulphur-containing compounds from A. sativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…Specifically, garlic is an excellent source of beneficial minerals, such as selenium, while onions are rich in flavonoids, such as quercetin, which is widely known for its biological properties [ 3 ]. Nevertheless, the most important bioactive compounds in the Alliaceae family are organosulfur compounds, mainly allyl cysteine derivatives, S-alk(en)yl-L-cysteine sulfoxides, thiosulfinates, thiosulfonates and sulfides, which are biosynthesized during tissue damage and confer useful biological properties, such as antimicrobial, anti-inflammatory, immunomodulatory, antioxidant, hepatoprotective and neuroprotective properties [ 3 , 4 , 5 ]. In fact, it is well described that these plants have cardioprotective effects that are associated with a positive effect on obesity and its associated metabolic disorders, including dyslipidemia, mild hypertension, hyperlipidemia, high blood glucose levels, impaired insulin sensitivity and liver lipotoxicity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, garlic is an excellent source of beneficial minerals, such as selenium, while onions are rich in flavonoids, such as quercetin, which is widely known for its biological properties [ 3 ]. Nevertheless, the most important bioactive compounds in the Alliaceae family are organosulfur compounds, mainly allyl cysteine derivatives, S-alk(en)yl-L-cysteine sulfoxides, thiosulfinates, thiosulfonates and sulfides, which are biosynthesized during tissue damage and confer useful biological properties, such as antimicrobial, anti-inflammatory, immunomodulatory, antioxidant, hepatoprotective and neuroprotective properties [ 3 , 4 , 5 ]. In fact, it is well described that these plants have cardioprotective effects that are associated with a positive effect on obesity and its associated metabolic disorders, including dyslipidemia, mild hypertension, hyperlipidemia, high blood glucose levels, impaired insulin sensitivity and liver lipotoxicity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…OSCs are the most important class of bioactive compounds in Alliaceae, which are synthesized during tissue damage in Allium as part of the defence mechanism against foreign aggressions. OSCs confer biological properties that are beneficial for health, such as antibacterial, antifungal, antiviral, antiprotozoal, anti-inflammatory, antidiabetic, antioxidant, antimutagenic, hepatoprotective or neuroprotective activities, among others [52][53][54][55][56][57][58]. The main OSCs in the genus Allium include the precursors S-alk(en)yl-L-cysteine sulphoxides (ACSO), whose transformation leads to thiosulfinates, thiosulfonates and sulfides in variable amounts and types.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies on anticancer drugs showed that garlic has reduced the proliferation of various types of cancer, such as skin, colon, stomach, lungs, breast, and prostate, by reducing carcinogenesis, including mutations, cell proliferation, and differentiation [ 31 ]. Compounds contained in garlic, including allicin, ajoene, diallyl sulfide, diallyl disulfide, and diallyl trisulfide contribute to the distinct flavors and odors and the prevention of various diseases and cancers [ 32 ]. However, there have been no studies on the analysis of bioactive compounds in A. sativum stem and their effects on cancer growth and metastasis, so there is a high need for analyzing the ingredients of A. sativum stem and evaluation of anticancer effects.…”
Section: Introductionmentioning
confidence: 99%